2011
DOI: 10.1111/j.1742-4658.2011.08083.x
|View full text |Cite
|
Sign up to set email alerts
|

Structure, signaling mechanism and regulation of the natriuretic peptide receptor guanylate cyclase

Abstract: Summary Atrial natriuretic peptide (ANP) and homologous B-type natriuretic peptide (BNP) are cardiac hormones that dilate blood vessels and stimulate natriuresis and diuresis, thereby lowering blood pressure and blood volume. ANP and BNP counterbalance the actions of the renin-angiotensin-aldosterone and neurohormonal systems, and play a central role in cardiovascular regulation. These activities are mediated by the A-type natriuretic peptide receptor (NPRA), a single transmembrane segment, guanylate cyclase (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
61
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(65 citation statements)
references
References 85 publications
3
61
0
1
Order By: Relevance
“…Interestingly, the chloride binding site at group II and III mGlu receptors is structurally conserved at ANP receptors (Acher et al, 2011;Misono et al, 2011). While chloride is not an agonist of ANP receptors, chloride has been shown to modulate ANP receptor oligimerization (Ogawa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, the chloride binding site at group II and III mGlu receptors is structurally conserved at ANP receptors (Acher et al, 2011;Misono et al, 2011). While chloride is not an agonist of ANP receptors, chloride has been shown to modulate ANP receptor oligimerization (Ogawa et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…For example, the kainate receptors require a chloride ion between protomers to facilitate dimerization (Chaudhry et al, 2009). It has also been shown that the binding of atrial natriuretic peptide (ANP) to ANP receptors requires chloride (Misono et al, 2011), and that the presence of chloride influences ANP receptor oligimerization (Ogawa et al, 2010). Interestingly, it has been reported that the ANP receptor chloride binding site is structurally conserved at mGlu receptors (Ogawa et al, 2010;Acher et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Natriuretic peptides are secreted by the ventricles of the heart, and they have been established as diagnostic and prognostic tools for cardiovascular diseases (Levin et al, 1998;Potter et al, 2009). B-type natriuretic peptide (BNP), originally isolated from porcine brain, binds to transmembrane natriuretic peptide receptor A (NPRA) (Mukoyama et al, 1991;Misono et al, 2011). A recent study reported that BNP-NPRA signaling is a key mechanism of itch transmission in the mouse spinal cord (Mishra and Hoon, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…It is now well established that ANP plays a major role in cardiovascular regulation through their natriuretic, diuretic, and vasorelaxant activities, as well as the end -organ activities that suppress cardiac hypertrophy and fibrosis and cardiomyocyte apoptosis 16) . In fetuses, levels of ANP are higher than in adults 17) .…”
Section: Discussionmentioning
confidence: 99%